PROFITABILITAS PADA PERUSAHAAN SYARIAH DI DAFTAR EFEK SYARIAH - Baining, Mellya Embun; Aryani, Lusiana (J-ISCAN: Journal of Islamic Accounting Research., 2021)
The purpose of this study was to determine the effect of cash turnover, inventory turnover and total asset turnover on profitability in Islamic companies in the list of sharia effects in the consumer goods industry sector in 2019. This study uses independent variables, namely cash turnover, inventory turnover and total asset turnover. The dependent variable is profitability. The data used in this study are secondary data, namely in the form of financial reports of Islamic companies in the consumer goods industry sector in 2018 and 2019. The year 2018 is used to compare 2019. This research is descriptive with a quantitative approach. Statistical mode using multiple linear regression analysis, t test, f test, and coefficient of determination analysis. The results of this study indicate that cash turnover and total asset turnover have an effect on profitability. Inventory turnover has no effect on profitability. By using the F test, it is found that the independent variable has a simultaneous influence on the dependent variable. The calculation of the coefficient of determination shows that all independent variables, namely cash turnover, inventory turnover and total assets turnover can explain the profitability variable of 36.7%, the remaining 63.3% is influenced by other variables not examined in this study.